Fiber-reinforced resin composite and thermoplastic resin foam sheet for fiber-reinforced resin composite

The fiber-reinforced resin composite with a thermoplastic resin foam layer and compatible polyester and polyimide resins addresses the heat resistance issues of existing thermoplastic polyester resin foam sheets, providing enhanced strength and handling without additional processing steps, suitable for diverse applications.

JP7609635B2Active Publication Date: 2025-01-07SEKISUI PLASTICS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020217887
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-25
Publication Date
2025-01-07
Estimated Expiration
2040-12-25

AI Technical Summary

Technical Problem

Existing thermoplastic polyester resin foam sheets used in food containers lack sufficient heat resistance strength, leading to softening and handling difficulties when heated, and require additional heat-setting steps or equipment investments.

Method used

A fiber-reinforced resin composite is developed, comprising a thermoplastic resin foam layer made of compatible polyester and polyimide resins, with a fiber-reinforced resin layer on both sides, achieving a single glass transition temperature and enhanced heat resistance through specific composition ratios and properties.

Benefits of technology

The composite exhibits excellent heat resistance strength without a heat-setting step, improving handling and reducing weight while maintaining structural integrity, suitable for various applications including transportation equipment and construction materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609635000012
    Figure 0007609635000012
  • Figure 0007609635000013
    Figure 0007609635000013
  • Figure 0007609635000014
    Figure 0007609635000014
Patent Text Reader

Abstract

To provide a fiber-reinforced resin composite body which is excellent in heat-resistant strength.SOLUTION: A fiber-reinforced resin composite body 2 has a sheet-like thermoplastic resin foam layer 5, and a fiber-reinforced resin layer 7 positioned on one surface or both surfaces of the thermoplastic resin foam layer 5, in which the thermoplastic resin foam layer 5 contains a polyester-based resin and a polyimide-based resin, and a glass transition temperature Tg of the thermoplastic resin foam layer 5 is single. The fiber-reinforced resin composite body 2 preferably has the glass transition temperature Tg of 80-130°C.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fiber-reinforced resin composite and a thermoplastic resin foam sheet for a fiber-reinforced resin composite. [Background technology]

[0002] 2. Description of the Related Art Conventionally, resin foam sheets obtained by foaming thermoplastic resins such as polystyrene-based resins and molded articles thereof have been used for food containers and the like because of their characteristics of being lightweight and having high thermal insulation properties. The market for ready-made meals, where prepared foods are purchased from convenience stores, supermarkets, and other retailers and eaten at home, is expanding. In the ready-made meal market, there is a demand for food containers that can be used for cooking in a microwave oven. Food containers that can be used for cooking need to be resistant to deformation when heated in a microwave oven, etc. (excellent dimensional stability when heated) and be easy to handle after heating without becoming soft (excellent heat resistance).

[0003] In response to such demands, for example, Patent Document 1 proposes a method for forming a foamed PET sheet in which a foamed polyethylene terephthalate (PET) sheet with a low degree of crystallinity is preheated to soften the foamed PET sheet, and then the sheet is molded in a mold at a temperature equal to or higher than that which promotes crystallization. According to the invention of Patent Document 1, the foamed PET sheet is heated to a temperature equal to or higher than that which promotes crystallization, thereby crystallizing the PET and improving the dimensional stability upon heating. However, the invention of Patent Document 1 requires a step (heat setting step) for promoting crystallization, which lengthens the molding time. In addition, the invention of Patent Document 1 requires an apparatus capable of heating to a temperature for promoting crystallization, which has problems such as requiring new capital investment.

[0004] To address these problems, Patent Document 2 proposes a thermoplastic polyester resin foam sheet containing a specific ratio of a crystalline polyester resin and an amorphous polyester resin having a specific glass transition temperature Tg. According to the invention of Patent Document 2, a container with excellent dimensional stability upon heating can be obtained without requiring a heat setting process. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 3-239527 [Patent Document 2] JP 2014-28920 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the invention of Patent Document 2 has low heat resistance strength, and therefore the molded product obtained by heating the thermoplastic polyester resin foamed sheet is soft and weak, making it difficult to handle.

[0007] Therefore, an object of the present invention is to provide a fiber-reinforced resin composite having excellent heat resistant strength. [Means for solving the problem]

[0008] As a result of intensive research by the present inventors, it was found that a mixture of a crystalline polyester resin and an amorphous polyester resin is not sufficiently compatible with each other, and therefore when the glass transition temperature of the lower of the two polyester resins is reached, the mixture softens and deforms. Based on this finding, it was found that the heat resistance strength can be increased by including two resins with high compatibility. As a result, it was found that when a thermoplastic resin foam layer and a fiber reinforced resin layer containing a fiber reinforced resin are combined to form a fiber reinforced resin composite, the heat resistance strength of the fiber reinforced resin composite can also be increased, and the present invention was completed.

[0009] That is, the present invention has the following aspects. [1] A sheet-shaped thermoplastic resin foam layer; A fiber reinforced resin layer located on one or both sides of the thermoplastic resin foam layer, the thermoplastic resin foam layer contains a polyester-based resin and a polyimide-based resin, The thermoplastic resin foam layer has a single glass transition temperature Tg. [2] The fiber-reinforced resin composite according to [1], wherein the glass transition temperature Tg is 80 to 130°C. [3] The fiber-reinforced resin composite according to [1] or [2], wherein the thermoplastic resin foam layer has an absolute value of 3 to 35 J / g between the amount of heat absorbed and the amount of heat generated, as determined by heat flux differential scanning calorimetry at a heating rate of 10°C / min. [4] The fiber-reinforced resin composite according to any one of [1] to [3], wherein a slope of an exponential approximation equation of a storage modulus E' between the glass transition temperature Tg and the glass transition temperature Tg+20°C in solid viscoelasticity measurement at a heating rate of 5°C / min and a frequency of 1 Hz is -0.18 to -0.025. [5] The fiber-reinforced resin composite according to any one of [1] to [4], wherein the polyimide-based resin is a polyetherimide-based resin. [6] The fiber-reinforced resin composite according to any one of [1] to [5], wherein the polyester-based resin contains a plant-derived polyester-based resin. [7] The content ratio of the polyester-based resin to the total mass of the thermoplastic resin contained in the thermoplastic resin foam layer is 40 to 95 mass%, The fiber-reinforced resin composite according to any one of [1] to [6], wherein the content ratio of the polyimide resin to the total mass of the thermoplastic resin contained in the thermoplastic resin foam layer is 5 to 60 mass %. [8] The fiber-reinforced resin composite according to any one of [1] to [7], wherein the thermoplastic resin foam layer contains recycled materials.

[0010] [9] A thermoplastic resin foam sheet for a fiber-reinforced resin composite used to form a thermoplastic resin foam layer of a fiber-reinforced resin composite having a sheet-shaped thermoplastic resin foam layer and a fiber-reinforced resin layer located on one or both sides of the thermoplastic resin foam layer, the thermoplastic resin foam layer contains a polyester-based resin and a polyimide-based resin, The thermoplastic resin foam sheet for a fiber-reinforced resin composite, wherein the thermoplastic resin foam layer has a single glass transition temperature Tg.

[10] The thermoplastic resin foam sheet for a fiber-reinforced resin composite according to [9], wherein the glass transition temperature Tg is 80 to 130°C.

[11] The thermoplastic resin foam sheet for a fiber-reinforced resin composite according to [9] or

[10] , wherein the absolute value of the difference between the amount of heat absorbed and the amount of heat generated, as determined by heat flux differential scanning calorimetry at a heating rate of 10°C / min, is 3 to 35 J / g.

[12] The thermoplastic resin foam sheet for a fiber-reinforced resin composite according to any one of [9] to

[11] , wherein a slope of an exponential approximation equation of a storage modulus E' between the glass transition temperature Tg and the glass transition temperature Tg+20°C in solid viscoelasticity measurement at a heating rate of 5°C / min and a frequency of 1 Hz is -0.18 to -0.025.

[13] The thermoplastic resin foam sheet for a fiber-reinforced resin composite according to any one of [9] to

[12] , wherein the polyimide-based resin is a polyetherimide-based resin.

[14] The thermoplastic resin foam sheet for a fiber-reinforced resin composite according to any one of [9] to

[13] , wherein the polyester-based resin contains a plant-derived polyester-based resin.

[15] The content ratio of the polyester-based resin to the total mass of the thermoplastic resin contained in the thermoplastic resin foam layer is 40 to 95 mass%, The thermoplastic resin foam sheet for a fiber-reinforced resin composite according to any one of [9] to

[14] , wherein a content ratio of the polyimide-based resin to a total mass of the thermoplastic resin contained in the thermoplastic resin foam layer is 5 to 60 mass%.

[16] The thermoplastic resin foam sheet for a fiber-reinforced resin composite according to any one of [9] to

[15] , wherein the thermoplastic resin foam layer contains recycled materials. Effect of the Invention

[0011] The fiber-reinforced resin composite of the present invention has excellent heat resistance strength. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a fiber-reinforced resin composite according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a flow diagram showing an example of a process for producing a plant-derived polyester resin. [Diagram 3] FIG. 1 is a flow diagram showing an example of a process for producing a plant-derived polyester resin. [Figure 4] FIG. 1 is a flow diagram showing an example of a process for producing a plant-derived polyester resin. [Diagram 5] FIG. 1 is a schematic diagram showing an example of a manufacturing apparatus for a thermoplastic resin foam layer according to an embodiment of the present invention. [Figure 6] 1 is a schematic cross-sectional view showing a manufacturing method of a fiber-reinforced resin composite according to one embodiment of the present invention. FIG. [Figure 7] 13 is a graph showing the results of measuring the storage modulus E′ of the thermoplastic resin foam layer before compounding used in producing the fiber-reinforced resin composite of Example 10. [Figure 8] 1 is a graph showing the results of measuring the storage modulus E′ of a foamed thermoplastic resin layer before compounding, used in producing a fiber-reinforced resin composite of Comparative Example 1. [Figure 9] 1 is a DSC curve of a thermoplastic resin foam layer before compounding used in the production of a fiber-reinforced resin composite of Example 10. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In this specification, the symbol "to" indicates a range that includes both ends of the symbol as the lower limit and upper limit. A preferred embodiment of the present invention will be described below by taking as an example a fiber-reinforced resin composite having fiber-reinforced resin layers located on both sides of a sheet-like thermoplastic resin foam layer. The fiber-reinforced resin composite may have fiber-reinforced resin layers on both sides of the thermoplastic resin foam layer, or may have a fiber-reinforced resin layer on one side of the thermoplastic resin foam layer. The thermoplastic resin foam layer of the fiber-reinforced resin composite may be composed of a single foam layer, or may have two or more foam layers.

[0014] [Fiber-reinforced resin composite] The fiber-reinforced resin composite of the present invention has a sheet-like thermoplastic resin foam layer and a fiber-reinforced resin layer located on one or both sides of the thermoplastic resin foam layer. The thermoplastic resin foam layer contains a polyester resin and a polyimide resin.

[0015] The fiber-reinforced resin composite has excellent heat resistance and mechanical strength, and can be used in a wide range of applications as a component for transport equipment. In addition, the fiber-reinforced resin composite can also be suitably used as a construction material, a windmill blade, a robot arm, a cushioning material for helmets, a transport container such as an agricultural box or a thermal insulation container, a rotor blade for an industrial helicopter, or a packaging material for parts. Examples of transport equipment components include structural members constituting the main body of transport equipment such as automobiles, aircraft, railroad cars, ships, etc. Examples of structural members constituting the main body of an automobile include door panels, door inners, bumpers, fenders, fender supports, engine covers, roof panels, trunk lids, floor panels, center tunnels, crash boxes, cowls, etc. For example, when a fiber-reinforced resin composite is used for a door panel that has conventionally been made of steel plate, the door panel has substantially the same rigidity as a steel plate door panel and can be significantly lighter, thereby reducing the weight of the automobile. One embodiment of a fiber reinforced resin composite will be described with reference to the drawings.

[0016] 1 is a cross-sectional view of a fiber-reinforced resin composite 2 of the present embodiment. The fiber-reinforced resin composite 2 has a sheet-like thermoplastic resin foamed layer 5 and fiber-reinforced resin layers 7 located on both sides of the thermoplastic resin foamed layer 5.

[0017] Thickness T of fiber-reinforced resin composite 2 2 can be determined taking into consideration the application. For example, if the fiber reinforced resin composite 2 is used for molding a container, the thickness T 2 The thickness T is preferably 0.3 to 5.0 mm, more preferably 0.4 to 3.0 mm, and further preferably 0.5 to 2.5 mm. 2 When the thickness T is equal to or greater than the lower limit, the impact resistance and rigidity of the container can be improved. 2When it is equal to or less than the above upper limit, the moldability of the fiber reinforced resin composite 2 can be improved. Thickness T 2 can be measured, for example, using a dial thickness gauge.

[0018] <Thermoplastic resin foam layer> The thermoplastic resin foam layer (hereinafter, simply referred to as "foam layer") 5 is a sheet-like foam layer (foam sheet). The foam layer 5 is formed by foaming a thermoplastic resin composition. The thermoplastic resin composition contains a thermoplastic resin and a foaming agent. The foamed layer 5 formed by foaming the thermoplastic resin composition contains two or more bubbles in a matrix formed of the thermoplastic resin.

[0019] The thermoplastic resin of the foam layer 5 contains a polyester-based resin and a polyimide-based resin. By containing both a polyester-based resin and a polyimide-based resin, the fiber-reinforced resin composite 2 of the present embodiment can have increased heat resistance strength.

[0020] <Polyester resin> Examples of polyester resins include polyethylene terephthalate resin (PET), polybutylene terephthalate resin (PBT), polyethylene naphthalate resin (PEN), polyethylene furanoate resin (PEF), polybutylene naphthalate resin (PBN), polytrimethylene terephthalate resin (PTT), copolymers of terephthalic acid, ethylene glycol and cyclohexane dimethanol, and mixtures thereof. As polyester resins, polyethylene terephthalate resin is preferred, and crystalline polyethylene terephthalate resin (C-PET) is more preferred. C-PET is a polyester resin in which the acid component is terephthalic acid and the glycol component is ethylene glycol. The polyester resin may be a polyester resin derived from a petrochemical product, a plant-derived polyester resin such as so-called bio-PET, or a mixture of these. Examples of plant-derived polyester resins include polyethylene terephthalate resins, plant-derived polyethylene furanoate resins, and plant-derived polytrimethylene terephthalate resins. The polyester resin may be made from recycled materials. These polyester resins may be used alone or in combination of two or more.

[0021] Hereinafter, the plant-derived polyester resin will be described. Plant-derived polyester resins are polymers derived from plant materials such as sugar cane and corn. "Derived from plant materials" includes polymers synthesized or extracted from plant materials. For example, "derived from plant materials" includes polymers obtained by polymerizing monomers synthesized or extracted from plant materials. "Monomers synthesized or extracted from plant materials" includes monomers synthesized using compounds synthesized or extracted from plant materials as raw materials. Plant-derived polyester resins include those in which some of the monomers are "derived from plant materials".

[0022] We will explain plant-derived polyester resins using PET and PEF as examples.

[0023] The synthesis reaction of PET is shown in formula (I). PET is synthesized by the dehydration reaction of n moles of ethylene glycol and n moles of terephthalic acid (Benzen-1,4-dicarboxylic acid). The stoichiometric mass ratio in this synthesis reaction is ethylene glycol:terephthalic acid = 30:70 (mass ratio).

[0024] [ka]

[0025] [In formula (I), n is a stoichiometric coefficient (degree of polymerization) and is a number from 250 to 1100.]

[0026] Ethylene glycol is produced industrially by oxidizing ethylene and hydrating it, and terephthalic acid is produced industrially by oxidizing paraxylene. As shown in Figure 2, when ethylene is obtained by the dehydration reaction of plant-derived ethanol (bioethanol), and PET is synthesized from ethylene glycol (bioethanol-derived ethylene glycol) and terephthalic acid derived from petrochemicals, the PET produced is 30% plant-derived by mass. Furthermore, as shown in Figure 3, when paraxylene is obtained by the dehydration reaction of plant-derived isobutanol (bioisobutanol) and PET is synthesized from terephthalic acid synthesized from this paraxylene and ethylene glycol derived from bioethanol, the PET produced is 100% plant-derived PET by mass.

[0027] The synthesis reaction of PEF is shown in formula (II). PEF is synthesized by the dehydration reaction of n moles of ethylene glycol and n moles of 2,5-furandicarboxylic acid.

[0028] [ka]

[0029] [In formula (II), n is a stoichiometric coefficient (degree of polymerization) and is a number from 250 to 1100.]

[0030] Furandicarboxylic acid (FDCA) can be obtained, for example, by dehydrating plant-derived fructose or glucose to obtain hydroxymethylfurfural (HMF), and then oxidizing the HMF. As shown in FIG. 4, when both FDCA and ethylene glycol are plant-derived, the produced PEF is 100% by mass plant-derived PEF.

[0031] The glass transition temperature Tg1 of the polyester resin is preferably 50 to 100°C, more preferably 60 to 90°C, and even more preferably 70 to 85°C. When Tg1 is equal to or higher than the lower limit, the heat resistance and the dimensional stability upon heating can be further improved. When Tg1 is equal to or lower than the upper limit, the molding cycle can be shortened to increase the productivity and improve the moldability. Note that "moldability" refers to, for example, the ability of a foamed sheet to conform to the cavity of a mold and approach a desired shape when the foamed sheet is sandwiched between the molds and thermoformed, and the closer the foamed sheet is to the desired shape, the "better" the moldability. The glass transition temperature Tg1 of the polyester resin is determined by heat flux differential scanning calorimetry (DSC) measurement during the second heating process at a heating rate of 10° C. / min.

[0032] The melting point of the polyester resin is preferably 230 to 270° C., more preferably 240 to 260° C., and even more preferably 245 to 255° C. When the melting point is equal to or higher than the lower limit, the heat resistance and the heat dimensional stability can be further improved. When the melting point is equal to or lower than the upper limit, the molding cycle can be shortened to increase the productivity and the moldability can be improved.

[0033] The intrinsic viscosity (IV value) of the polyester resin is preferably 0.5 to 1.5, more preferably 0.6 to 1.3, and even more preferably 0.7 to 1.2. When the IV value is equal to or more than the lower limit, cell breakage during foaming is suppressed, and the open cell ratio can be further reduced. When the IV value is equal to or less than the upper limit, the density can be further reduced, the surface can be made smoother, and the beauty of the appearance can be improved. The IV value can be measured according to the method of JIS K7367-5 (2000).

[0034] The number average molecular weight Mn of the polyester resin is preferably from 9,000 to 26,000, more preferably from 15,000 to 26,000, and even more preferably from 20,000 to 25,000. When Mn is equal to or more than the lower limit, the cold resistance (i.e., mechanical strength at low temperatures) can be further improved. When Mn is equal to or less than the upper limit, the heat resistance can be further improved.

[0035] The Z-average molecular weight Mz of the polyester resin is preferably from 100,000 to 500,000, more preferably from 150,000 to 450,000, and even more preferably from 200,000 to 400,000. When Mz is within the above range, the cold resistance (that is, the mechanical strength at low temperatures) can be further improved.

[0036] Mn and Mz can be measured by the following method. (Molecular weight of polyester resin) Take 5 mg of sample from the measurement target, add 0.5 mL of hexafluoroisopropanol (HFIP) and 0.5 mL of chloroform in that order, and shake gently by hand. Leave it for 24 ± 1.0 hours. After confirming that the sample is completely dissolved, dilute it to 10 mL with chloroform and shake gently by hand to mix. Then, filter it with a non-aqueous 0.45 μm chromato disk made by GL Sciences Inc. or a non-aqueous 0.45 μm syringe filter made by Shimadzu GLC Co., Ltd. to obtain the measurement sample. Measure the measurement sample with a chromatograph under the following measurement conditions, and obtain the number average molecular weight Mn and Z average molecular weight Mz of the sample from the standard polystyrene calibration curve prepared in advance.

[0037] [Measuring device] Measurement equipment: Tosoh Corporation's "HLC-8320GPC EcoSEC" gel permeation chromatograph (with built-in RI and UV detectors). [GPC measurement conditions] ·column <Sample side> Guard column = 1x TSK guardcolumn HXL-H (6.0mm x 4.0cm) manufactured by Tosoh Corporation. Measurement column: Tosoh Corporation's TSKgel GMHXL (7.8 mm I.D. x 30 cm) x 2 in series. <Reference side> Two resistance tubes (inner diameter 0.1 mm x 2 m) in series. Column temperature = 40°C. Mobile phase = chloroform. <Dynamic phase flow rate> Sample side pump = 1.0 mL / min. Reference pump = 0.5 mL / min. Detector = UV detector (254 nm). Injection volume = 15 μL. Measurement time = 26 min. Sampling pitch = 500 ms.

[0038] [Standard polystyrene sample for calibration curve] The standard polystyrene samples for the calibration curve are those manufactured by Showa Denko K.K. under the product names "STANDARD SM-105" and "STANDARD SH-75" and have mass average molecular weights Mw of 5,620,000, 3,120,000, 1,250,000, 442,000, 131,000, 54,000, 20,000, 7,590, 3,450, and 1,320. The above standard polystyrene for the calibration curve is grouped into A (5,620,000, 1,250,000, 131,000, 20,000, 3,450) and B (3,120,000, 442,000, 54,000, 7,590, 1,320). A is weighed (2 mg, 3 mg, 4 mg, 4 mg, 4 mg) and dissolved in 30 mL of chloroform. B is weighed (3 mg, 4 mg, 4 mg, 4 mg, 4 mg) and dissolved in 30 mL of chloroform. The standard polystyrene calibration curve is obtained by injecting 50 μL of each of the prepared solutions A and B, and creating a calibration curve (cubic equation) from the retention times obtained after measurement. The number average molecular weight Mn and Z average molecular weight Mz are calculated using the calibration curve.

[0039] The content of the polyester resin relative to the total mass of the thermoplastic resin contained in the foam layer 5 is preferably 40 to 95 mass%, more preferably 50 to 90 mass%, and even more preferably 60 to 80 mass%. When the content of the polyester resin is equal to or more than the lower limit, moldability can be improved. When the content of the polyester resin is equal to or less than the upper limit, heat resistance strength can be further improved.

[0040] <Polyimide resin> The polyimide resin is not particularly limited, but is preferably a polymer containing a cyclic imide group as a repeating unit, and is preferably a polymer having melt moldability. Examples of polyimide-based resins include polyetherimides described in U.S. Pat. No. 4,141,927, Japanese Patent No. 2,622,678, Japanese Patent No. 2,606,912, Japanese Patent No. 2,606,914, Japanese Patent No. 2,596,565, Japanese Patent No. 2,596,566, and Japanese Patent No. 2,598,478, and the like; Examples of such polymers include those described in Japanese Patent Publication No. 2599171, Japanese Patent Publication No. 9-48852, Japanese Patent No. 2565556, Japanese Patent No. 2564636, Japanese Patent No. 2564637, Japanese Patent No. 2563548, Japanese Patent No. 2563547, Japanese Patent No. 2558341, Japanese Patent No. 2558339, and Japanese Patent No. 2834580. The main chain of the polyimide resin may contain structural units other than cyclic imide as long as the effects of the present invention are not impaired. Examples of structural units other than the cyclic imide include aromatic, aliphatic, alicyclic, alicyclic ester units, and oxycarbonyl units. The polyimide resin may be made from recycled materials. These polyimide resins may be used alone or in combination of two or more.

[0041] The polyimide resin is preferably, for example, a compound represented by the following formula (III).

[0042] [ka]

[0043] [In formula (III), R is an aromatic group having 6 to 42 carbon atoms, and R' is at least one divalent organic group selected from the group consisting of a divalent aromatic group having 6 to 30 carbon atoms, an aliphatic group having 2 to 30 carbon atoms, and an alicyclic group having 4 to 30 carbon atoms. p is a number representing a repeating unit and is 5 to 100.]

[0044] As the polyimide-based resin, a polyetherimide-based resin having a structural unit having an ether bond is preferred from the viewpoint of improving compatibility with polyester-based resins.

[0045] The polyimide resin can be prepared by a conventionally known manufacturing method. For example, it can be obtained by dehydration condensation of either or both of tetracarboxylic acid and its acid anhydride, which are raw materials capable of deriving R in formula (III), and one or more compounds selected from the group consisting of aliphatic primary diamines and aromatic primary diamines, which are raw materials capable of deriving R' in formula (III). Specific examples of the manufacturing method of the polyimide resin include a method of obtaining a polyamic acid and then subjecting it to thermal ring closure. Alternatively, examples of the manufacturing method include a method of chemically closing the ring using an acid anhydride and a chemical ring-closing agent such as pyridine or carbodiimide, and a method of heating the tetracarboxylic anhydride and a diisocyanate capable of deriving R' to decarbonation and polymerization.

[0046] Examples of tetracarboxylic acids include pyromellitic acid, 1,2,3,4-benzenetetracarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,2',3,3'-biphenyltetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 2,2',3,3'-benzophenonetetracarboxylic acid, bis(2,3-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl)methane, 1,1'-bis(2,3-dicarboxyphenyl)ethane, and 2,2'-bis(3,4-dicarboxyphenyl) Examples of such acid anhydrides include propane, 2,2'-bis(2,3-dicarboxyphenyl)propane, bis(3,4-dicarboxyphenyl)ether, bis(2,3-dicarboxyphenyl)ether, bis(3,4-dicarboxyphenyl)sulfone, bis(2,3-dicarboxyphenyl)sulfone, 2,3,6,7-naphthalenetetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic acid, 1,2,5,6-naphthalenetetracarboxylic acid, 2,2'-bis[(2,3-dicarboxyphenoxy)phenyl]propane, and acid anhydrides thereof.

[0047] Examples of diamines include benzidine, diaminodiphenylmethane, diaminodiphenylethane, diaminodiphenylpropane, diaminodiphenylbutane, diaminodiphenylether, diaminodiphenylsulfone, diaminodiphenylbenzophenone, o, m, p-phenylenediamine, tolylenediamine, xylylenediamine, and aromatic primary diamines having a hydrocarbon group of these aromatic primary diamines as a structural unit, ethylenediamine, 1,2-propanediamine, 1,3-propanediamine, 2,2-dimethyl-1,3-propanediamine, 1,6-hexamethylenediamine, 1,8 Examples of the diamine include 1,9-octamethylenediamine, 1,10-decamethylenediamine, 1,11-undecamethylenediamine, 1,12-dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 1,4-cyclohexanedimethylamine, 2-methyl-1,3-cyclohexanediamine, isophoronediamine, and the like, as well as aliphatic and alicyclic primary diamines having a hydrocarbon group as a structural unit of these aliphatic and alicyclic primary diamines.

[0048] The glass transition temperature Tg2 of the polyimide resin is preferably 190 to 240° C., more preferably 200 to 230° C., and even more preferably 210 to 220° C. When Tg2 is equal to or higher than the lower limit, the heat resistance and the heated dimensional stability can be further improved. When Tg2 is equal to or lower than the upper limit, the molding cycle can be shortened to increase the productivity and improve the moldability. The glass transition temperature Tg2 of the polyimide resin is determined in the same manner as the glass transition temperature Tg1 of the polyester resin.

[0049] The melt flow rate (MFR) of the polyimide resin is preferably 3 to 30 g / 10 min, more preferably 5 to 25 g / 10 min, and even more preferably 7 to 20 g / 10 min. When the MFR is equal to or higher than the lower limit, the molding cycle can be shortened to increase productivity and moldability. When the MFR is equal to or lower than the upper limit, heat resistance and dimensional stability under heat can be further increased. In this specification, MFR is a value at 337° C. and 6.6 kgf, and can be measured in accordance with the method described in ASTM D1238.

[0050] The number average molecular weight of the polyimide resin is preferably 5,000 to 50,000, more preferably 6,000 to 39,000, and even more preferably 7,000 to 27,000. When the number average molecular weight of the polyimide resin is equal to or more than the lower limit, the impact resistance can be further improved. When the number average molecular weight of the polyimide resin is equal to or less than the upper limit, the moldability can be further improved. The number average molecular weight of the polyimide resin is determined by gel permeation chromatography (GPC) using polyethylene oxide as a standard substance.

[0051] The content of the polyimide resin in the total mass of the thermoplastic resin contained in the foam layer 5 is preferably 5 to 60 mass%, more preferably 10 to 50 mass%, and even more preferably 20 to 40 mass%. When the content of the polyimide resin is equal to or more than the lower limit, the heat resistance strength can be further improved. When the content of the polyimide resin is equal to or less than the upper limit, the moldability can be further improved.

[0052] When it is necessary to know the content of the polyimide resin in the foam layer 5, the content of the polyimide resin can be measured, for example, by the method shown below. The foamed layer 5 is sliced ​​along a direction (planar direction) perpendicular to the thickness direction of the foamed layer 5 to prepare a thin sample (for example, a sample having a thickness of 0.2 mm). The content of polyimide resin in this sample is measured. An example of a method for measuring the content of polyimide resin relative to the total mass of a mixed resin of polyester resin and polyimide resin is given below. In the following measurement method, polyethylene terephthalate (PET) is used as the polyester resin, and polyetherimide (PEI) is used as the polyimide resin.

[0053] (Method for measuring the content of polyimide resin) The foamed layer 5 is sliced ​​to a size of 0.2 mm from the surface of the foamed layer 5 along a direction (planar direction) perpendicular to the thickness direction to prepare a measurement sample. The surface of the measurement sample is subjected to infrared spectroscopy (IR) analysis under the following conditions to obtain an infrared absorption spectrum. Measurement equipment: Thermo SCIENTIFIC's Nicolet iS10 Fourier transform infrared spectrophotometer and Thermo SCIENTIFIC's single reflection horizontal ATR Smart-iTR. ATR Crystal: Diamond attached KRS-5 (angle = 42°). ·Measurement method: Single reflection ATR method. ·Measurement wavenumber range: 4000cm -1 ~400cm -1 . Wavenumber dependence of measurement depth: not corrected. · Detector: Deuterated triglycine sulfate (DTGS) detector and KBr beam splitter. ·Resolution: 4cm -1 . -Number of accumulations: 16 (same for background measurement).

[0054] From the obtained infrared absorption spectrum chart, the peak heights of D1410 and D1778 are obtained, and the content of polyimide resin is calculated from the following formula obtained from a calibration curve prepared using a standard sample. Polyimide resin content (wt%) = 100 - {19.00ln(R) + 37.95} x 100 R=D1410 / D1778

[0055] D1410 is a polyester resin with a wave number of 1410 cm -1 ±5cm -1 The maximum absorbance difference (measured absorbance - baseline absorbance) from the baseline in the infrared absorption spectrum curve in the region of 1400 cm. The baseline is the wave number of 1400 cm in the infrared absorption spectrum curve. -1 ±5cm -1 The position of the minimum absorption at 1420 cm in the infrared absorption spectrum curve -1 ±5cm -1It is a straight line connecting the position of minimum absorption at D1778 is a polyimide resin with a wave number of 1778 cm -1 ±5cm -1 The maximum absorbance difference (measured absorbance - baseline absorbance) from the baseline in the infrared absorption spectrum curve in the region of 1760 cm -1 ±5cm -1 The position of the minimum absorption at 1800 cm and the wave number in the infrared absorption spectrum curve -1 ±5cm -1 It is a straight line connecting the position of minimum absorption at

[0056] The above standard sample can be prepared as follows.

[0057] (Preparation of standard samples) First, according to the formulation shown in Table 1, a polyester resin (PET: manufactured by Far East New Century Co., Ltd., product name "CH-653"), a polyimide resin (PEI: manufactured by SABIC Innovative Plastics, product name "Ultem1000"), and pyromellitic anhydride (PMDA) are mixed to prepare a mixture. The mixture is charged into a Labo Plastomill twin-screw extruder (manufactured by Toyo Seiki Seisakusho Co., Ltd., model: 2DC15W, aperture 15 mm, L / D = 17) and melt-kneaded at 350 ° C to obtain a resin composition. The resin composition is extruded from a nozzle die (diameter 3.0 mm) attached to the front end of the Labo Plastomill twin-screw extruder. The extruded resin composition is immediately cooled in a cooling water tank. Then, the cooled strand-shaped resin composition is thoroughly drained, and then cut into small pellets with a length of about 2 mm and a diameter of about 3 mm using a pelletizer to prepare standard samples (A to I). The compositions of the standard samples (A to I) are shown in Table 1.

[0058] [Table 1]

[0059] The above calibration curve is prepared as follows.

[0060] (Creating a calibration curve) The surfaces of the standard samples (A to I) are subjected to infrared spectroscopic analysis under the following conditions to obtain infrared absorption spectra. Measurement equipment: Thermo SCIENTIFIC's Nicolet iS10 Fourier transform infrared spectrophotometer and Thermo SCIENTIFIC's single reflection horizontal ATR Smart-iTR. ATR Crystal: Diamond attached KRS-5 (angle = 42°). ·Measurement method: Single reflection ATR method. ·Measurement wavenumber range: 4000cm -1 ~400cm -1 . Wavenumber dependence of measurement depth: not corrected. · Detector: Deuterated triglycine sulfate (DTGS) detector and KBr beam splitter. ·Resolution: 4cm -1 . -Number of accumulations: 16 (same for background measurement). Number of measurements: 10.

[0061] From the infrared absorption spectrum chart obtained in each measurement, data processing is performed in the same manner as when determining the content ratio of polyimide resin, the peak heights of D1410 and D1778 are obtained, and the absorbance ratio (R = D1410 / D1778) is calculated. The blending ratio of polyester resin against the absorbance ratio of each standard sample (A to I) is plotted, and the logarithmic approximation formula in the plot is used as the calibration curve.

[0062] The thermoplastic resin contained in the foam layer 5 may contain recycled materials. Either the polyester resin or the polyimide resin may contain recycled materials, or both the polyester resin and the polyimide resin may contain recycled materials. A part or all of the polyester resin may be recycled raw materials for polyester resin, or a part or all of the polyimide resin may be recycled raw materials for polyimide resin. Examples of recycled raw materials include the following raw materials: 1) The foam layer (foamed body) is crushed to obtain flake-like resin, which is then remelted in an extruder and extruded in the form of strands from a nozzle die. These are then cooled and pelletized to produce recovered pellets. 2) Recycled PET made by crushing PET bottles to obtain flake-like resin, which is then remelted in an extruder and extruded into strands through a nozzle die, which are then cooled and pelletized.

[0063] <Other resins> The foam layer 5 is substantially free of a thermosetting resin. "Substantially free" means that the thermosetting resin is not contained at all or is contained to an extent that does not affect the quality of the foam layer 5. The content of the thermosetting resin in the foam layer 5 is preferably 5 parts by mass or less, more preferably 2 parts by mass or less, even more preferably 1 part by mass or less, and most preferably 0 part by mass, relative to 100 parts by mass of the thermoplastic resin.

[0064] The thermoplastic resin may include a thermoplastic resin (other thermoplastic resin) other than the polyester resin and the polyimide resin. Examples of the other thermoplastic resin include polyolefin resins such as polyethylene and polypropylene, polystyrene resins, polyphenylene ether resins, polyamide resins, polycarbonate resins, polyarylate resins, polyphenylsulfone resins, polysulfone resins, and polyethersulfone resins.

[0065] The total proportion of the polyester resin and the polyimide resin relative to the total mass of the thermoplastic resin is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, and most preferably 100% by mass. When the total proportion of the polyester resin and the polyimide resin is equal to or more than the lower limit, the heat resistance strength of the foamed layer 5 can be further increased.

[0066] <Physical Properties> The foam layer 5 has a single glass transition temperature Tg. The polyester resin and the polyimide resin are compatible with each other, resulting in a single glass transition temperature Tg. The foam layer 5 has a single glass transition temperature Tg, which is higher than the glass transition temperature Tg1 of the polyester resin, thereby increasing the heat resistance. The term "single glass transition temperature" means that the glass transition temperature at a lower temperature side than the crystallization peak observed in the second heating process can be recognized as single in a heat flux differential scanning calorimetry chart (DSC curve) at a heating rate of 10°C / min. However, if no crystallization peak is observed in the second heating process, it means that the glass transition temperature in the temperature range (30 to 300°C) in the second heating process can be recognized as single. The glass transition temperature Tg of the foamed layer 5 is, for example, preferably 80 to 130° C., more preferably 85 to 125° C., and even more preferably 90 to 120° C. When Tg is equal to or higher than the lower limit, the heat resistance and the heated dimensional stability can be further improved. When Tg is equal to or lower than the upper limit, the molding cycle can be shortened to increase the productivity, and the moldability can be improved. The glass transition temperature Tg of the foamed layer 5 is determined by DSC measurement during the second heating process at a heating rate of 10° C. / min. The glass transition temperature Tg of the foamed layer 5 can be regarded as the same as the glass transition temperature Tg of the thermoplastic resin constituting the foamed layer 5.

[0067] The absolute value of the difference between the amount of heat absorbed and the amount of heat generated in the foamed layer 5 (endothermic heat generation difference) is preferably 3 to 35 J / g, more preferably 5 to 30 J / g, and even more preferably 7 to 28 J / g. When the endothermic heat generation difference is equal to or greater than the lower limit, the degree of crystallization is increased, and the heat resistant strength and dimensional stability upon heating can be further improved. When the endothermic heat generation difference is equal to or less than the upper limit, the degree of crystallization does not increase too much, and moldability can be improved. The endothermic / heat-generating difference is the difference between the amount of heat absorbed and the amount of heat generated, determined by DSC measurement during the first heating process at a heating rate of 10° C. / min. The heat absorption / heat generation difference in the foam layer 5 can be regarded as the same as the heat absorption / heat generation difference of the thermoplastic resin constituting the foam layer 5.

[0068] In the foamed layer 5, the slope r of the exponential approximation equation of the storage modulus E' between the glass transition temperature Tg and the glass transition temperature Tg+20°C in solid viscoelasticity measurement at a heating rate of 5°C / min and a frequency of 1 Hz (hereinafter also simply referred to as "slope r") is preferably -0.18 to -0.025, more preferably -0.15 to -0.030, and further preferably -0.10 to -0.035. When the slope r is equal to or greater than the lower limit, the change in the storage modulus E' associated with an increase in temperature is small, and the heat resistant strength can be further improved. When the slope r is equal to or less than the upper limit, the change in the storage modulus E' associated with an increase in temperature is not too small, and the moldability can be further improved. The slope r of the exponential approximation equation for the storage modulus E' is the coefficient r of x in the following equation (e).

[0069] y = p × exp(r × x) (e) y: Storage modulus E' (Pa) x: Temperature (℃) p: y value at x=0 (Pa)

[0070] The crystallinity of the foamed layer 5 is preferably 2 to 25%, and more preferably 3 to 21%. When the crystallinity of the foamed layer 5 is equal to or higher than the lower limit, the heat resistant strength and the heated dimensional stability can be further improved. When the crystallinity of the foamed layer 5 is equal to or lower than the upper limit, the moldability is improved, and a fiber reinforced resin composite 2 having a beautiful appearance can be obtained. The crystallinity of the foamed layer 5 is determined by the method described in the Examples.

[0071] <Foaming agent> Examples of the blowing agent include saturated aliphatic hydrocarbons such as propane, normal butane, isobutane, normal pentane, isopentane, and hexane, ethers such as dimethyl ether, fluorocarbons such as methyl chloride, 1,1,1,2-tetrafluoroethane, 1,1-difluoroethane, and monochlorodifluoromethane, carbon dioxide, and nitrogen, and dimethyl ether, propane, normal butane, isobutane, carbon dioxide, and nitrogen are preferred. These blowing agents may be used alone or in combination of two or more.

[0072] The content of the foaming agent is not particularly limited, but is preferably, for example, 0.1 to 12 parts by mass with respect to 100 parts by mass of the thermoplastic resin.

[0073] <Optional ingredients> The foam layer 5 of the present embodiment may contain other components (optional components) in addition to the thermoplastic resin and the foaming agent. Optional components include cell regulators, stabilizers, UV absorbers, colorants, antioxidants, crystallization accelerators, lubricants, crosslinking agents, surfactants, shrinkage inhibitors, flame retardants, and deterioration inhibitors.

[0074] Examples of the cell regulator include mixtures of inorganic powders such as talc and silica, etc. These cell regulators increase the closed cell ratio of the foamed layer 5, making it easier to form the foamed layer 5. The content of the cell regulator is preferably, for example, 0.2 to 5 parts by mass with respect to 100 parts by mass of the thermoplastic resin.

[0075] Examples of the stabilizer include calcium zinc-based heat stabilizers, tin-based heat stabilizers, and lead-based heat stabilizers. The content of the stabilizer is preferably, for example, 1 part by mass or less with respect to 100 parts by mass of the thermoplastic resin.

[0076] Examples of the ultraviolet ray absorbent include cesium oxide-based ultraviolet ray absorbents and titanium oxide-based ultraviolet ray absorbents. The content of the ultraviolet absorbing agent is preferably, for example, 1 part by mass or less with respect to 100 parts by mass of the thermoplastic resin.

[0077] Examples of colorants include titanium oxide, carbon black, titanium yellow, iron oxide, ultramarine blue, cobalt blue, calcined pigments, metallic pigments, mica, pearl pigments, zinc oxide, precipitated silica, and cadmium red. The content of the colorant is, for example, preferably 2 parts by mass or less with respect to 100 parts by mass of the thermoplastic resin.

[0078] Examples of the antioxidant include cerium oxide, cerium oxide / zirconia solid solution, cerium hydroxide, carbon, carbon nanotubes, titanium oxide, and fullerene. The content of the antioxidant is preferably, for example, 1 part by mass or less with respect to 100 parts by mass of the thermoplastic resin.

[0079] Examples of the crystallization promoter include silicates, carbon, metal oxides, etc. Examples of the silicates include talc, which is hydrated magnesium silicate. Examples of the carbon include carbon black, carbon nanofiber, carbon nanotubes, carbon nanohorns, activated carbon, graphite, graphene, coke, mesoporous carbon, glassy carbon, hard carbon, soft carbon, etc. Examples of the carbon black include furnace black, acetylene black, ketjen black, thermal black, etc. Examples of the metal oxide include zinc oxide, titanium oxide, etc. The content of the crystallization promoter is, for example, preferably 3 parts by mass or less with respect to 100 parts by mass of the thermoplastic resin.

[0080] Examples of the crosslinking agent include acid dianhydrides such as pyromellitic anhydride, polyfunctional epoxy compounds, oxazoline compounds, oxazine compounds, etc. By blending a crosslinking agent in the thermoplastic resin composition, cell breakage during foaming is suppressed, and the open cell ratio can be further reduced. The content of the crosslinking agent is preferably, for example, 0.08 to 0.8 parts by mass with respect to 100 parts by mass of the thermoplastic resin.

[0081] The above-mentioned optional components may each be used alone or in combination of two or more. The total amount of the optional components contained in the foamed layer 5 is preferably from 0.1 to 5 parts by mass, and more preferably from 0.5 to 3 parts by mass, based on the total mass of the foamed layer 5.

[0082] The open cell ratio of the foamed layer 5 is preferably 20% or less, more preferably 18% or less, and even more preferably 16% or less. When the open cell ratio of the foamed layer 5 is equal to or less than the above upper limit, the impact resistance of the molded body of the fiber reinforced resin composite 2 can be further improved, and the moldability can be further improved. The lower limit of the open cell ratio of the foamed layer 5 is not particularly limited, but 0% is preferable. The open cell ratio of the foamed layer 5 is determined by the method described in JIS K7138:2006 "Rigid foamed plastics-Determination of open cell ratio and closed cell ratio."

[0083] The basis weight of the foam layer 5 is, for example, 50 to 900 g / m 2 is preferable, and 100 to 700 g / m 2 More preferably, 150 to 600 g / m 2 is more preferable. When the basis weight of the foamed layer 5 is equal to or more than the above lower limit, the impact resistance of the molded body of the fiber reinforced resin composite 2 can be further improved. When the basis weight of the foamed layer 5 is equal to or less than the above upper limit, the fiber reinforced resin composite 2 can be made lighter. In addition, when the basis weight of the foamed layer 5 is equal to or less than the above upper limit, the heating time during hot molding is not too long, and the productivity of the molded body of the fiber reinforced resin composite 2 can be further improved.

[0084] The basis weight of the foam layer 5 can be measured by the following method. Excluding 20 mm from both ends in the width direction of the foam layer 5, five or more pieces of 10 cm x 10 cm are cut out at equal intervals in the width direction, and the mass (g) of each piece is measured to the nearest 0.001 g. The average mass (g) of each piece is calculated by dividing the mass (g) by the mass (g) of the entire foam layer by 1 m. 2 The value converted into the mass per unit area is the basis weight (g / m2) of the foam layer 5. 2 )

[0085] The apparent density of the foam layer 5 is, for example, 0.050 to 0.666 g / cm 3 is preferable, and 0.066 to 0.500 g / cm 3 More preferably, 0.100 to 0.400 g / cm 3When the apparent density of the foamed layer 5 is equal to or more than the above lower limit, the heat insulating property and impact resistance of the molded article of the fiber-reinforced resin composite 2 can be further improved. When the apparent density of the foamed layer 5 is equal to or less than the above upper limit, the fiber-reinforced resin composite 2 can be made lighter.

[0086] The expansion ratio of the foamed layer 5 is, for example, preferably 2 to 30, more preferably 3 to 20, and further preferably 3.5 to 15. When the expansion ratio of the foamed layer 5 is equal to or more than the above lower limit, the heat insulating property and impact resistance of the molded article of the fiber reinforced resin composite 2 can be further improved. When the expansion ratio of the foamed layer 5 is equal to or less than the above upper limit, the moldability of the fiber reinforced resin composite 2 can be further improved. The expansion ratio of the foamed layer 5 can be determined in the same manner as described in the examples.

[0087] The average cell diameter of the foamed layer 5 is, for example, preferably 80 to 1000 μm, more preferably 150 to 750 μm, and even more preferably 200 to 500 μm. When the average cell diameter of the foamed layer 5 is equal to or more than the above lower limit, the impact resistance of the fiber reinforced resin composite 2 can be further improved. When the average cell diameter of the foamed layer 5 is equal to or less than the above upper limit, the surface smoothness of the fiber reinforced resin composite 2 can be further improved. The average cell diameter of the foamed layer 5 can be measured in accordance with the method described in ASTM D2842-69.

[0088] Thickness T of foam layer 5 5 can be determined taking into consideration the application. For example, if the fiber reinforced resin composite 2 is used for molding a container, the thickness T 5 The thickness T is preferably 0.3 to 5.0 mm, more preferably 0.4 to 3.0 mm, and further preferably 0.5 to 2.5 mm. 5 When the thickness T is equal to or greater than the lower limit, the impact resistance and rigidity of the molded body of the fiber-reinforced resin composite 2 can be improved. 5 When it is equal to or less than the above upper limit, the moldability of the fiber reinforced resin composite 2 can be improved. Thickness T 5 can be measured, for example, using a dial thickness gauge.

[0089] <Fiber reinforced resin layer> The fiber reinforced resin layer 7 is a skin material provided on both sides of the foam layer 5. By including the fiber reinforced resin layer 7, the fiber reinforced resin composite 2 has superior mechanical strength. The fibers constituting the fiber-reinforced resin layer 7 are not particularly limited, and examples thereof include carbon fibers, glass fibers, aramid fibers, boron fibers, metal fibers, etc. Because of their excellent mechanical strength and heat resistance, the fibers constituting the fiber-reinforced resin layer 7 are preferably carbon fibers, glass fibers, and aramid fibers, and more preferably carbon fibers.

[0090] The form of the fiber reinforced resin layer 7 is not particularly limited, and examples thereof include woven fabric, knitted fabric, nonwoven fabric, and a surface material formed by binding (sewing) fiber bundles (strands) in which fibers are aligned in one direction with synthetic resin threads such as polyamide resin, polyester resin, etc., or stitch threads such as glass fiber thread, etc. Examples of the weaving method of the fabric include plain weave, twill weave, satin weave, etc.

[0091] The fiber-reinforced resin layer 7 may be (1) a multilayer panel formed by laminating a plurality of sheets of woven fabric, knitted fabric, or nonwoven fabric together or in any combination thereof, or (2) a multilayer panel formed by overlapping a plurality of panel sheets formed by bundling (stitching) fiber bundles (strands) in which the fibers are aligned in one direction with a stitch thread such as a synthetic resin thread of polyamide-based resin, polyester-based resin, or a glass fiber thread, so that the fiber directions of the fiber bundles are oriented in different directions, and integrating (stitching) the overlapped panel sheets together with a stitch thread such as a synthetic resin thread of polyamide-based resin, polyester-based resin, or a glass fiber thread.

[0092] Examples of the resin contained in the fiber-reinforced resin layer 7 include uncured thermosetting resins and thermoplastic resins. The thermosetting resin is not particularly limited, and examples thereof include epoxy resins, unsaturated polyester resins, phenol resins, melamine resins, polyurethane resins, silicon resins, maleimide resins, vinyl ester resins, cyanate ester resins, and resins obtained by prepolymerizing maleimide resins and cyanate ester resins. As the thermosetting resin, epoxy resins and vinyl ester resins are preferred because they have excellent heat resistance, elastic modulus, and chemical resistance. The thermosetting resin may contain additives such as a curing agent and a curing accelerator. The thermosetting resin may be used alone or in combination of two or more types. The thermoplastic resin is not particularly limited, and examples thereof include polyolefin resins such as polyethylene resins and polypropylene resins, acrylic resins, polyester resins, polyamide resins, and polycarbonate resins.

[0093] The content of the resin in the fiber reinforced resin layer 7 is preferably 20 to 70 mass %, and more preferably 30 to 60 mass %, based on the total mass of the fiber reinforced resin layer 7. When the resin content is equal to or greater than the above lower limit, the bonds between the fibers are improved, and the mechanical strength of the obtained fiber reinforced resin composite 2 is increased. When the resin content is equal to or less than the above upper limit, the amount of resin present between the fibers is not too large, and the mechanical strength of the fiber reinforced resin layer 7 is increased, and the mechanical strength of the obtained fiber reinforced resin composite 2 is increased.

[0094] The method for impregnating the fiber reinforced resin layer 7 with the resin is not particularly limited, and examples thereof include (1) a method of immersing the fibers in the resin, and (2) a method of applying the resin to the fibers.

[0095] In this embodiment, the materials of the fiber reinforced resin layers 7 located on both sides of the foam layer 5 may be the same or different.

[0096] Thickness T of the fiber-reinforced resin layer 7 7The thickness T of the fiber-reinforced resin layer 7 is preferably 0.1 to 5 mm, and more preferably 0.3 to 3 mm. 7 When the thickness T of the fiber-reinforced resin layer 7 is equal to or greater than the above lower limit, the mechanical strength of the fiber-reinforced resin composite 2 can be further increased. 7 When is equal to or less than the above upper limit value, the fiber reinforced resin composite 2 can be further reduced in weight. In this embodiment, the thickness T of the fiber-reinforced resin layer 7 located on both sides of the foam layer 5 7 may be the same as or different from each other.

[0097] The fiber reinforced resin layer 7 has a weight per unit area of, for example, 50 to 4000 g / m 2 is preferable, and 100 to 1000 g / m 2 It is more preferable that the fiber reinforced resin layer 7 has a basis weight of at least the above lower limit, which can further increase the mechanical strength of the fiber reinforced resin composite 2. The fiber reinforced resin layer 7 has a basis weight of at most the above upper limit, which can further reduce the weight of the fiber reinforced resin composite 2.

[0098] [Method of manufacturing fiber-reinforced resin composite] The fiber-reinforced resin composite 2 is produced by a conventionally known production method. The fiber-reinforced resin composite 2 is produced by first producing the foamed layer 5, and then providing the fiber-reinforced resin layer 7 on the surface of the foamed layer 5. The foamed layer (foamed sheet) 5 can be produced, for example, by the following method. 5 is an apparatus for producing a foamed sheet by extrusion molding (co-extrusion method). The production apparatus 1 includes an extruder 10, a foaming agent supply source 18, a circular die 20, a mandrel 30, and two winders 40. The extruder 10 is a so-called tandem type extruder. The extruder 10 includes a first extrusion section 11 and a second extrusion section 12 connected to the first extrusion section 11 via a pipe 16. The first extrusion section 11 includes a hopper 14. A foaming agent supply source 18 is connected to the first extrusion section 11. A circular die 20 is connected to the second extrusion section 12. A mandrel 30 having a cutter 32 is provided downstream of the circular die 20. A cooling blower (not shown) is provided between the circular die 20 and the mandrel 30. The extruder 10 of the production apparatus 1 may be an extruder other than a tandem extruder. For example, the extruder 10 may be an extruder in which a circular die 20 is connected to the first extrusion section 11. The extruder 10 of the production apparatus 1 may be a single screw extruder or a multi-screw extruder such as a twin screw extruder.

[0099] The raw material constituting the foam layer is fed from a hopper 14 to the first extrusion section 11. The raw material fed from the hopper 14 includes the resin constituting the foam layer and any optional components that are mixed as necessary. In the first extrusion section 11, the raw materials are mixed while being heated to a given temperature to form a resin melt, and a foaming agent is supplied from a foaming agent supply source 18 to the first extrusion section 11, and the foaming agent is mixed with the resin melt to form a resin composition. The heating temperature is appropriately determined in consideration of the type of resin, etc., so long as the resin melts and the optional components are not denatured.

[0100] The glass transition temperature Tg1 of the polyester resin (raw polyester resin) blended in the thermoplastic resin composition is preferably 50 to 100°C, more preferably 60 to 90°C, and even more preferably 70 to 85°C. When Tg1 is equal to or higher than the lower limit, the heat resistance and the dimensional stability upon heating can be further improved. When Tg1 is equal to or lower than the upper limit, the molding cycle can be shortened to increase the productivity and improve the moldability. Note that "moldability" refers to, for example, when a foamed sheet is sandwiched between a mold and thermoformed, the foamed sheet can conform to the cavity of the mold and approach a desired shape, and the closer to the desired shape, the "better" the moldability.

[0101] The melting point of the raw material polyester resin is preferably 230 to 270° C., more preferably 240 to 260° C., and even more preferably 245 to 255° C. When the melting point is equal to or higher than the lower limit, the heat resistance and the heat dimensional stability can be further improved. When the melting point is equal to or lower than the upper limit, the molding cycle can be shortened to increase the productivity and the moldability can be improved.

[0102] The intrinsic viscosity (IV value) of the raw material polyester resin is preferably 0.5 to 1.5, more preferably 0.6 to 1.3, and even more preferably 0.7 to 1.2. When the IV value is equal to or more than the lower limit, the breakage of cells during foaming can be suppressed, and the open cell ratio can be further reduced. When the IV value is equal to or less than the upper limit, the density can be further reduced, the surface can be made smoother, and the beauty of the appearance can be improved. The IV value can be measured according to the method of JIS K7367-5 (2000).

[0103] The number average molecular weight Mn of the raw material polyester resin is preferably from 9,000 to 26,000, more preferably from 15,000 to 26,000, and even more preferably from 20,000 to 25,000. When Mn is equal to or more than the lower limit, the cold resistance (i.e., mechanical strength at low temperatures) can be further improved. When Mn is equal to or less than the upper limit, the heat resistance can be further improved.

[0104] The Z-average molecular weight Mz of the raw material polyester resin is preferably from 100,000 to 500,000, more preferably from 150,000 to 450,000, and even more preferably from 200,000 to 400,000. When Mz is within the above range, the cold resistance (that is, the mechanical strength at low temperatures) can be further improved.

[0105] The thermoplastic resin composition is supplied from the first extrusion section 11 through the pipe 16 to the second extrusion section 12, where it is further mixed. Thereafter, the resin composition is cooled to a given temperature and then guided to a resin flow path in the circular die 20. The thermoplastic resin composition guided to the resin flow path is extruded from the circular die 20, and the foaming agent foams the composition to form a cylindrical foamed sheet 5a. The cylindrical foamed sheet 5a is guided to the mandrel 30 while being blown with cooling air sent from a cooling blower. The cylindrical foamed sheet 5a passes over the outer surface of the mandrel 30, is cooled to a desired temperature, and is cut into two pieces by the cutter 32 to become the foamed sheet 5. The foamed sheet 5 is wrapped around a guide roll 42 and a guide roll 44, respectively, and is taken up by the winder 40 to become the foamed sheet roll 4.

[0106] The method of providing the fiber reinforced resin layer 7 on the surface of the foam layer 5 is not particularly limited, and examples thereof include (1) a method of laminating and bonding the fiber reinforced resin layer 7 on the surface of the foam layer 5 via an adhesive, (2) a method of laminating a fiber reinforced resin layer 7 impregnated with a thermoplastic resin on the surface of the foam layer 5, and bonding the fiber reinforced resin layer 7 to the surface of the foam layer 5 using the thermoplastic resin as a binder, (3) a method of laminating a fiber reinforced resin layer 7 impregnated with an uncured thermosetting resin on the surface of the foam layer 5, and bonding the fiber reinforced resin layer 7 to the foam layer 5 using a cured product of the thermosetting resin as a binder, and (4) a method of laminating a fiber reinforced resin layer 7 in a heated and softened state on the surface of the foam layer 5, and pressing the fiber reinforced resin layer 7 against the surface of the foam layer 5 to bond the fiber reinforced resin layer 7 to the foam layer 5. In the method (4), it is also possible to deform the fiber reinforced resin layer 7 along the surface of the foam layer 5. Here, since the foam layer 5 of this embodiment has excellent load resistance in a high-temperature environment, the method (4) can also be preferably used. By these methods, the fiber reinforced resin layer 7 can be integrally provided on the surface of the foam layer 5. Methods for joining the fiber reinforced resin layer 7 to the surface of the foam layer 5 include, for example, an autoclave method, a hand lay-up method, a spray-up method, a PCM (Prepreg Compression Molding) method, an RTM (Resin Transfer Molding) method, and a VaRTM (Vacuum assisted Resin Transfer Molding) method.

[0107] The method of bonding the fiber reinforced resin layer 7 to the surface of the foam layer 5 (hereinafter, also referred to as "composite formation") will be described more specifically with reference to FIG. As shown in FIG. 6, a fiber reinforced resin layer 7 is laminated on the surface of a foam layer 5 to form a laminate 6. Further, the breather cloth 70 is laminated on the fiber reinforced resin layer 7 of the laminate 6 via the release film 60. In FIG. 6, the breather cloth 70 laminated on the upper surface of the laminate 6 is laminated on the fiber reinforced resin layer 7 of the laminate 6 via the release film 60 so as to cover the side surface of the laminate 6 as well. The breather cloth 70 is preferably laminated on the upper surface of the laminate 6 so as to cover both side surfaces of the laminate 6, and more preferably laminated so as to cover the entire surface of the laminate 6. By laminating the breather cloth 70 in this manner, the excess thermosetting resin in the fiber reinforcement material 7 laminated on both sides of the foam layer 5 can be absorbed and removed by one breather cloth 70. Note that FIG. 6 shows a case where the breather cloth 70 is laminated only on one fiber reinforced resin layer 7 via the release film 60, but the breather cloth 70 may be laminated on both fiber reinforced resin layers 7 via the release film 60. In addition, the breather cloth 70 does not necessarily have to cover the side surface of the laminate 6.

[0108] The release film 60 is configured to be easily peelable from the fiber reinforced resin layer 7. The release film 60 is made of a synthetic resin film. Since excess thermosetting resin impregnated in the fiber reinforced resin layer 7 can be smoothly absorbed by the breather cloth 70, it is preferable that the release film 60 has through holes formed therein that penetrate from the front to the back surface. If no through holes are formed in the release film 60 , excess thermosetting resin impregnated in the fiber reinforced resin layer 7 is absorbed by the breather cloth 70 through the outside of the release film 60 . When a large number of through holes penetrating from the front to the back surface are formed in the release film 60, excess thermosetting resin impregnated in the fiber reinforced resin layer 7 can be absorbed into the breather cloth 70 through the through holes of the release film 60. Examples of synthetic resins constituting the release film 60 include fluorine-based resins such as tetrafluoroethylene-ethylene copolymer (tetrafluoroethylene-ethylene copolymer).

[0109] The breather cloth 70 is used to absorb excess thermosetting resin impregnated in the fiber reinforced resin layer 7. The breather cloth 70 may be any cloth that does not deform or deteriorate when the laminate 6 is heated and pressed, and examples of the breather cloth include nonwoven fabrics. Examples of the nonwoven fabric include nonwoven fabrics made of amide resin fibers such as nylon fibers, polyester resin fibers, and glass cloths.

[0110] Next, the laminate 6 is placed on the mold 8, and the bagging film 50 is placed on the laminate 6 to seal the laminate 6. The release film 60 and the breather cloth 70 may be laminated on the mold 8 or before the laminate 6 is placed on the mold 8. The bagging film 50 is a film for sealing the laminate 6 and vacuuming the entire laminate 6. Examples of synthetic resins constituting the bagging film 50 include amide resins such as nylon. A sealant 9 is interposed between the entire periphery of the outer periphery of the bagging film 50 and the mold 8 to ensure airtightness. The laminate 6 may be formed by laminating fiber reinforced resin layers 7, 7 on the mold 8 inside the bagging film 50, impregnated with uncured thermosetting resin on the surface of the foam layer 5. The surface of the mold 8 on which the laminate 6 is placed is treated with a release treatment 81 so that the fiber reinforced resin layer of the obtained fiber reinforced resin composite can be easily peeled off.

[0111] In Figure 6, the laminate 6 is placed on the mold 8, and the bagging film 50 is placed over the laminate 6 to seal the laminate 6 with the bagging film 50. However, the bagging film 50 may be formed into a bag shape, the laminate 6 may be stored inside the bag-shaped bagging film 50, and the laminate 6 may be sealed with the bagging film 50.

[0112] Thereafter, the space 90 sealed with the bagging film 50 is evacuated to reduce the pressure therein. The degree of vacuum in the space 90 is preferably 0.08 to 0.14 MPa, more preferably 0.10 to 0.12 MPa. When the degree of vacuum in the space 90 is equal to or greater than the lower limit, the air present in the fiber reinforced resin layer 7 is sufficiently discharged, the generation of voids in the fiber reinforced resin layer 7 can be suppressed, and the decrease in the mechanical strength of the fiber reinforced resin composite 2 can be suppressed. When the degree of vacuum in the space 90 is equal to or less than the upper limit, the thermosetting resin impregnated in the fiber reinforced resin layer 7 can be suppressed from being sucked, and the decrease in the mechanical strength of the fiber reinforced resin layer 7 can be suppressed. As a result, the decrease in the mechanical strength of the fiber reinforced resin composite 2 can be suppressed.

[0113] Next, after depressurizing the space 90 sealed with the bagging film 50 or simultaneously with the start of depressurization, the laminate 6 in the space 90 is heated to soften the thermosetting resin in the fiber reinforced resin layer 7. After the thermosetting resin has softened, the laminate 6 is pressurized and the heating is continued. Note that it is preferable that the reduced pressure state in the space 90 is maintained while the laminate 6 is being heated and pressurized. The heating temperature when heating the laminate 6 is, for example, preferably 70 to 110° C., more preferably 80 to 100° C. When the heating temperature is equal to or higher than the above lower limit, the thermosetting resin in the fiber reinforced resin layer 7 can be sufficiently softened. When the heating temperature is equal to or lower than the above upper limit, deterioration of the laminate 6 can be suppressed.

[0114] The degree of pressurization (pressurizing pressure) of the laminate 6 is preferably 0.05 to 1.5 MPa, and more preferably 0.1 to 1.0 MPa. When the pressurizing pressure is equal to or greater than the lower limit, the air present in the fiber reinforced resin layer 7 is sufficiently discharged, the generation of voids in the fiber reinforced resin layer 7 can be suppressed, and the decrease in the mechanical strength of the fiber reinforced resin composite 2 can be suppressed. In addition, when the pressurizing pressure is equal to or greater than the lower limit, the thermosetting resin in the fiber reinforced resin layer 7 can be well blended throughout the fiber reinforced resin layer 7, and the decrease in the mechanical strength of the fiber reinforced resin layer 7 can be suppressed, and the decrease in the mechanical strength of the fiber reinforced resin composite 2 can be suppressed. When the pressurizing pressure is equal to or less than the upper limit, deformation of the foam layer 5 can be suppressed.

[0115] By pressurizing the laminate 6, air in the fiber reinforced resin layer 7 can be more reliably removed, and voids can be prevented from being generated in the fiber reinforced resin layer 7. In addition, by pressurizing the laminate 6, the adhesion between the fibers can be improved, and further, the fiber reinforced resin layer 7 can be pressed against the surface of the foamed layer 5 while deforming the fiber reinforced resin layer 7 along the surface of the foamed layer 5, so that the fiber reinforced resin layer 7 can be laminated in a state in which it is in close contact with the surface of the foamed layer 5 over the entire surface. In particular, even when corners or unevenness are formed on the surface of the foam layer 5, the fiber reinforced resin layer 7 can be pressed against the surface of the foam layer 5 while deforming the fiber reinforced resin layer 7 along the surface of the foam layer 5, so that the fiber reinforced resin layer 7 can be laminated in a state of being in close contact with the entire surface of the foam layer 5. Furthermore, when the fiber reinforcement 7 is laminated in a state of being in close contact along the surface of the foam layer 5, the air that was present at the interface between the fiber reinforced resin layer 7 and the surface of the foam layer 5 is almost completely eliminated, and the fiber reinforced resin layer 7 is in a state of being well in contact with the surface of the foam layer 5.

[0116] In addition, by applying pressure to the laminate 6, the thermosetting resin impregnated in the fiber-reinforced resin layer 7 is allowed to blend into the entire fibers, and the fibers can be reliably bound together with the minimum amount of thermosetting resin required. In this way, since the fibers can be bound together with the minimum amount of thermosetting resin required, no excess thermosetting resin is present between the fibers, and the fibers can be highly oriented, which improves the mechanical strength of the fiber-reinforced resin layer 7 and provides the fiber-reinforced resin layer 7 with an excellent appearance.

[0117] Furthermore, when the fiber reinforced resin layer 7 is a multi-layered surface material, the overlapping surface materials can be firmly integrated by pressure, and the mechanical strength of the obtained fiber reinforced resin composite 2 can be further increased.

[0118] On the other hand, by pressurizing the laminate 6, excess thermosetting resin impregnated in the fiber reinforced resin layer 7 may come to the surface of the fiber reinforced resin layer 7. In such a case, the excess thermosetting resin is absorbed by the breather cloth 70 through the outside of the release film 60 or through the through holes formed in the release film 60. Therefore, the surface of the fiber reinforced resin layer 7 of the obtained fiber reinforced resin composite 2 does not contain excess thermosetting resin and has excellent appearance. When the breather cloth 70 covers the side surface of the laminate 6, the excess thermosetting resin in the fiber reinforced resin layers 7, 7 laminated on both sides of the foam layer 5 can be reliably absorbed and removed by the breather cloth 70 by evacuating the space 90 sealed by the bagging film 50 from the laminate 6 in the direction of the breather cloth 70 covering the side surface of the laminate 6.

[0119] As described above, the laminate 6 continues to be heated while being pressed, and this heating hardens the thermosetting resin impregnated in the fiber reinforced resin layer 7 of the laminate 6. After the thermosetting resin has softened, the heating temperature of the laminate 6 may be the same or may be changed, but it is preferable to increase the heating temperature of the laminate 6 in order to promote hardening of the thermosetting resin.

[0120] As the thermosetting resin hardens, the fibers in the fiber-reinforced resin layer 7 are bonded and fixed to each other, and the fiber-reinforced resin layer 7 is laminated and integrated onto the surface of the foamed layer 5 by the thermosetting resin in a deformed state along the surface of the foamed layer 5, thereby obtaining the fiber-reinforced resin composite 2.

[0121] Next, the fiber-reinforced resin composite 2 is cooled and the pressure applied to the fiber-reinforced resin composite 2 is released, and then the back valve 35 is opened to release the reduced pressure in the space 90, and the space 90 is opened to remove the fiber-reinforced resin composite 2.

[0122] As shown in FIG. 1, in the obtained fiber-reinforced resin composite 2, the fibers are bonded together by the cured thermosetting resin, and the solidified fiber-reinforced resin layer 7 is laminated and integrated in a state in which it is in close contact with the surface of the foam layer 5.

[0123] [Thermoplastic resin foam sheet for fiber reinforced resin composites] The thermoplastic resin foam sheet for a fiber-reinforced resin composite of the present invention is used for forming a thermoplastic resin foam layer of a fiber-reinforced resin composite having a sheet-like thermoplastic resin foam layer and a fiber-reinforced resin layer located on one or both sides of the thermoplastic resin foam layer. The thermoplastic resin foam layer contains a polyester resin and a polyimide resin, and has a single glass transition temperature Tg. The thermoplastic resin foam sheet for a fiber-reinforced resin composite may be the above-mentioned foam sheet consisting of only the thermoplastic resin foam layer.

[0124] The thermoplastic resin and optional components of the thermoplastic resin foamed sheet for a fiber-reinforced resin composite are the same as those of the above-mentioned foamed layer 5. In addition, the physical properties such as the melting point, crystallization temperature, glass transition temperature, endothermic amount (a), heat generation amount (b), crystallinity, and slope r of the thermoplastic resin foamed sheet for a fiber-reinforced resin composite are the same as those of the above-mentioned foamed layer 5. The physical properties of the thermoplastic resin foamed sheet for a fiber-reinforced resin composite can be determined in the same manner as for the foamed layer 5 described above.

[0125] [Method of manufacturing thermoplastic resin foam sheet for fiber reinforced resin composite] The thermoplastic resin foam sheet for a fiber-reinforced resin composite can be produced by the same method as that for the foam layer 5 described above.

[0126] In the thermoplastic resin foam sheet for fiber-reinforced resin composites of the present invention, the polyester-based resin and the polyimide-based resin are compatible with each other, and the thermoplastic resin has a single glass transition temperature Tg, which is higher than the glass transition temperature Tg1 of the polyester-based resin, thereby improving the heat resistance strength. For this reason, the thermoplastic resin foam sheet of the present invention is suitable as a foam sheet for the above-mentioned fiber-reinforced resin composite.

[0127] In the foam layer 5 of this embodiment, the polyester resin and the polyimide resin are compatible with each other, and the glass transition temperature Tg of the thermoplastic resin is uniform, so that the glass transition temperature Tg is higher than the glass transition temperature Tg1 of the polyester resin, and the heat resistance strength is improved. Therefore, the fiber reinforced resin composite 2 in which the fiber reinforced resin layer 7 is laminated on the surface of the foam layer 5 has excellent heat resistance strength. In addition, the fiber reinforced resin composite 2 of the present embodiment exhibits excellent heat resistance without requiring a heat setting process, thereby improving the productivity of molded articles of the fiber reinforced resin composite. The fiber reinforced resin composite 2 of the present embodiment exhibits excellent heat resistance even when the crystallinity is less than 20%. Furthermore, since the fiber reinforced resin composite 2 of the present embodiment is produced through a heat setting process, the degree of crystallinity is increased, and the dimensional stability under heating is further improved. EXAMPLES

[0128] The present invention will be described below with reference to examples, but the present invention is not limited to these.

[0129] (Raw materials used) <Polyester resin> PET(A): Manufactured by Far Eastern New Century Co., Ltd., product name "CH-611", glass transition temperature: 78°C, melting point: 251°C, IV value: 1.04, biomass content: 0%. PET (B): Manufactured by INDRAMA, product name "RAMAPET N1B", glass transition temperature: 78°C, melting point: 247°C, IV value: 0.80, biomass content: 30%. PET(C): Manufactured by Far Eastern New Century Co., Ltd., product name "CH-653", glass transition temperature: 79°C, melting point: 248°C, IV value: 1.01, biomass content: 27-30%. PET(D): Manufactured by Far East Ishizuka Green Pet Co., Ltd., product name "CB-603RJ", glass transition temperature: 79°C, melting point: 248°C, IV value: 0.80, biomass content: 0%, recycled PET from PET bottles.

[0130] <Polyimide resin> PEI(A): Polyetherimide, manufactured by SABIC Innovative Plastics, product name "Ultem1000", glass transition temperature: 217°C, MFR: 9g / 10min. PEI(B): Polyetherimide, manufactured by SABIC Innovative Plastics, product name "Ultem1010", glass transition temperature: 217°C, MFR: 17.8g / 10min. PEI(C): Polyetherimide, manufactured by SABIC Innovative Plastics, product name "Ultem MD130", glass transition temperature: 217°C, MFR: 9g / 10min. Recovered pellets: The foamed sheet obtained in Example 7 was pulverized to obtain flake-like resin, which was then remelted in a twin-screw extruder and extruded from a nozzle die in the form of strands, which were then cooled and pelletized.

[0131] <Amorphous polyester resin> PCT(G): Eastman Chemical Company, trade name "Traitan TX-1001", aromatic dicarboxylic acid component = terephthalic acid, diol component = 1,4-cyclohexanedimethanol and 2,2,4,4-tetramethyl-1,3-cyclobutanediol, glass transition temperature: 107°C, IV value: 0.72.

[0132] <Talc masterbatch> Talc MB: A masterbatch consisting of 72% PET and 28% talc by mass.

[0133] <Crosslinking agent> · PMDA: Pyromellitic anhydride.

[0134] <Fiber reinforced resin layer> (A): Fiber-reinforced resin layer (A), a fiber-reinforced base material formed from a twill weave of carbon fiber, containing 50% by mass of uncured epoxy resin as a thermosetting resin (manufactured by Mitsubishi Chemical Corporation, product name "TR3110-392IMP", thickness 0.25 mm, basis weight 200 g / m 2 ). (B): Fiber-reinforced resin layer (B), glass fiber (manufactured by Mitsubishi Chemical Corporation, product name "GH2030-392GM", thickness 0.19 mm, basis weight 203 g / m 2 ).

[0135] (Evaluation method) <Thickness> The thickness of the foamed sheet before compounding, excluding 20 mm at both ends in the width direction (TD direction), was measured at nine equally spaced points in the width direction using a dial thickness gauge SM-112 (manufactured by Techlock Corporation), and the arithmetic mean of the measured values ​​was taken as the thickness.

[0136] <Basic weight> Excluding 20 mm from both ends of the width direction (TD) of the foamed sheet before compounding, six pieces of 10 cm x 10 cm were cut out at equal intervals in the width direction, and the mass (g) of each piece was measured to the nearest 0.001 g. The average mass (g) of each piece was calculated as 1 m. 2 The converted value is the basis weight (g / m2) of the foam sheet. 2 ) was decided.

[0137] <Apparent density> The calculation was made using the following formula (s1) from the basis weight and thickness of the foamed sheet before compounding. Apparent density (g / cm 3 )=Basic weight (g / m 2 ) ÷ thickness (mm) ÷ 1000 (s1)

[0138] <Expansion ratio> The density of the thermoplastic resin was calculated from the blending ratio of each example, and the density of the thermoplastic resin was divided by the apparent density of the foamed sheet before compounding to obtain the foaming ratio. The following values ​​were used for the density of each resin. PET: 1.35g / cm 3 . PEI: 1.28g / cm 3 . PCT: 1.18g / cm 3 .

[0139] <Open cell ratio> Two or more sheet-like samples measuring 25 mm long x 25 mm wide were cut out from the foamed sheet before compounding, and the cut out samples were stacked together so that there was no space between them to obtain a test piece with a thickness of 25 mm. The outer dimensions of the test piece were measured to the nearest 1 / 100 mm using a Mitutoyo Corporation "Digimatic Caliper" vernier caliper, and the apparent volume (V1: cm 3 Next, the volume of the test piece (V2: cm3) was measured using a Tokyo Science Co., Ltd. "1000" air comparison specific gravity meter by the 1-1 / 2-1 atmospheric pressure method. 3 ) was calculated. The open cell rate (%) was calculated using the following formula (s2), and the average open cell rate of the five test pieces was calculated. The test pieces were previously conditioned for at least 24 hours in a standard atmosphere of class 2, JIS K 7100:1999, "23 / 50" (temperature 23±2°C, relative humidity 50±5%), and then measured in the same standard atmosphere. The air comparison specific gravity meter was used with a standard ball (large 28.96 cm 3 , small 8.58cm 3 ) was used for correction. Open cell rate (%) = (V1-V2) / V1 × 100 (s2) (V1: apparent volume measured using a vernier caliper, V2: volume measured using an air comparison hydrometer)

[0140] <Melting point, crystallization temperature, glass transition temperature> The melting point, crystallization temperature and glass transition temperature were measured by the methods described in JIS K7121: 1987 and JIS K7121: 2012. However, the sampling method and temperature conditions were as follows. Samples cut from the foamed sheet before and after compounding were placed in the bottom of an aluminum measuring container at 5.5±0.5 mg without leaving any gaps, and then covered with an aluminum lid. Differential scanning calorimetry was then performed using a Hitachi High-Tech Science DSC7000X, AS-3 differential scanning calorimeter. The sample was heated and cooled in the following steps 1 to 4 under a nitrogen gas flow rate of 20 mL / min to obtain a DSC curve. (Step 1) Hold at 30°C for 2 minutes. (Step 2) The temperature is increased from 30°C to 300°C at a rate of 10°C / min (first temperature increase process) and held for 10 minutes. (Step 3) Quickly remove the sample and allow it to cool in an environment of 25±10℃. (Step 4) Heat from 30°C to 300°C at a rate of 10°C / min (second heating process). Alumina was used as the reference material. Using the analysis software attached to the device, the temperatures of the melting peak and the top of the crystallization peak observed during the second heating process were read as the melting point and the crystallization temperature, as shown in Figure 11. The glass transition temperature Tg was calculated as the midpoint glass transition temperature from the DSC curve observed during the second heating process, using the analysis software attached to the device. This midpoint glass transition temperature was obtained according to (9.3) described in JIS K7121:2012. The glass transition temperature Tg was determined as the glass transition temperature at a lower temperature than the crystallization peak observed in the second heating process in a heat flux differential scanning calorimetry chart (DSC curve) at a heating rate of 10°C / min. However, if no crystallization peak was observed in the second heating process, the glass transition temperature in the temperature range (30 to 300°C) in the second heating process was used.

[0141] <Amount of heat absorbed (a), amount of heat generated (b), degree of crystallinity> The endothermic amount (a) (heat of fusion) and the exothermic amount (b) (heat of crystallization) were measured by the methods described in JIS K7121: 1987 and JIS K7121: 2012. However, the sampling method and temperature conditions were as follows. Samples cut from the foamed sheet before and after compounding were placed in the bottom of an aluminum measuring container at 5.5±0.5 mg without leaving any gaps, and then covered with an aluminum lid. Differential scanning calorimetry was then performed using a Hitachi High-Tech Science DSC7000X, AS-3 differential scanning calorimeter. The sample was heated and cooled in the following steps 1 and 2 under a nitrogen gas flow rate of 20 mL / min to obtain a DSC curve. (Step 1) Hold at 30°C for 2 minutes. (Step 2) Heat from 30°C to 300°C at a rate of 10°C / min (first heating process). Alumina was used as the reference material. The endothermic heat (a) and the calorific heat (b) were calculated using the analysis software attached to the device. Specifically, as shown in Figure 9, the endothermic heat (a) was calculated from the area enclosed by the line connecting the point where the DSC curve leaves the low-temperature baseline and the point where the DSC curve returns to the high-temperature baseline, and the DSC curve. The calorific heat (b) was calculated from the area enclosed by the line connecting the point where the DSC curve leaves the low-temperature baseline and the point where the DSC curve returns to the high-temperature baseline, and the DSC curve. Both the endothermic heat (a) and the calorific heat (b) were obtained from the DSC curve during the first heating process. The crystallinity of each sample was calculated using the endothermic amount (a) and the exothermic amount (b) according to the following formula (s3). Degree of crystallinity (%) = {(absolute value of endothermic heat (a) (J / g) - absolute value of exothermic heat (b) (J / g)) ÷ heat of complete crystallization (J / g)} × 100 (s3) The heat of complete crystallization represents the amount of heat required for 100% crystallization. Note that the heat of complete crystallization in the above formula (s3) was 140.1 J / g, which is the heat of complete crystallization of PET.

[0142] <Solid viscoelasticity measurement> The solid viscoelasticity measurements were performed using an "EXSTRAR DMS6100" viscoelasticity spectrometer manufactured by SII Nano Technology Co., Ltd. Samples with a length of approximately 40 mm, a width of approximately 10 mm, and a thickness of approximately 1 mm were cut from the foamed sheets before and after compounding. The conditions were as follows: Mode: Tensile control mode. Atmosphere: Nitrogen atmosphere. Frequency: 1Hz Heating rate: 5℃ / min. ·Measurement temperature: 30℃~300℃. -Chuck spacing: 20mm. ·Distortion amplitude: 5μm. ·Minimum tension: 100mN. Tension Gain: 1.5 Initial force amplitude: 100mN. The analysis was performed using analysis software provided with the device. As shown in Fig. 7 and Fig. 8, the slope r was calculated from an exponential approximation equation using the value of the storage modulus E' between the glass transition temperature Tg and the glass transition temperature Tg + 20°C. Fig. 7 shows the measurement results of the foamed sheet used in the production of the fiber reinforced resin composite of Example 10 described later, and Fig. 8 shows the measurement results of the foamed sheet used in the production of the fiber reinforced resin composite of Comparative Example 1 described later. The glass transition temperature Tg was determined from the DSC curve in the second heating process. The dimensions of the test pieces were measured using a "DIGIMATIC" CD-15 type manufactured by Mitutoyo Corporation.

[0143] (Evaluation method) <High-temperature bending test: rate of change in elastic modulus> The bending strength was measured in accordance with JIS K7017:1999. The bending modulus was measured using Shimadzu Corporation's "Autograph AG-X plus 100kN" universal testing machine and Shimadzu Corporation's "TRAPEZIUM X" universal testing machine data processing. The size of the test piece was 15 mm wide x 100 mm long, and it was used for measurement after conditioning for 16 hours under the standard atmosphere of JIS K 7100:1999 symbol "23 / 50" (temperature 23°C, relative humidity 50%), class 2. After storage under the above conditions, the test piece was quickly set in the jig in the thermostatic chamber attached to the device under each specified temperature condition, and the test was started after 3 minutes. The test speed was 2.7 mm / min. The radius of the tip of the pressure wedge and the fulcrum was 5R, and the distance between the fulcrums was 80 mm. From the obtained graph, the load region where the slope was maximum was set, and the apparent flexural modulus was determined by the universal testing machine data processing. The rate of change in elastic modulus was calculated as the rate of change (%) from the apparent flexural modulus at room temperature (23° C.) using the following formula (s4). Change in elastic modulus (%) = apparent flexural modulus at any temperature (MPa) / apparent flexural modulus at 23°C (MPa) × 100 (s4)

[0144] The heat resistance strength of the fiber reinforced resin composite was evaluated based on the rate of change in elastic modulus and in accordance with the following evaluation criteria. Evaluation Criteria ◯: The rate of change in elastic modulus at 80° C. is 90% or more, the rate of change in elastic modulus at 100° C. is 60% or more, and the rate of change in elastic modulus at 120° C. is 20% or more. △: The rate of change in elastic modulus at 80°C is more than 80% and less than 90%, and the rate of change in elastic modulus at 120°C is 20% or more, or the rate of change in elastic modulus at 100°C is more than 40% and less than 60%, and the rate of change in elastic modulus at 120°C is 20% or more. ×: The rate of change in elastic modulus at 80° C. is 80% or less, the rate of change in elastic modulus at 100° C. is 40% or less, or the rate of change in elastic modulus at 120° C. is less than 20%.

[0145] <Appearance evaluation> The appearance of each fiber-reinforced resin composite was visually observed and evaluated based on the following criteria. Note that the recesses on the surface of the fiber-reinforced resin layer of the fiber-reinforced resin composite were defined as portions that were depressed due to non-uniform shrinkage of the foam sheet. Evaluation Criteria ◯: There were no recesses on the surface of the fiber-reinforced resin layer of the fiber-reinforced resin composite, and the appearance was beautiful. Δ: A small number of recesses were observed on the surface of the fiber-reinforced resin layer of the fiber-reinforced resin composite. ×: A large number of recesses were found on the surface of the fiber-reinforced resin layer of the fiber-reinforced resin composite, and the appearance was poor.

[0146] <Overall evaluation of fiber-reinforced resin composites> From the evaluation results of the heat resistance strength and appearance of the fiber-reinforced resin composites, the fiber-reinforced resin composites were comprehensively evaluated according to the following evaluation criteria. Evaluation Criteria ○: All items were rated as “○”. △: There were no "x" marks in the evaluation of any item, and at least one "△" mark in the evaluation of any item. ×: Any of the items was rated as “×”.

[0147] <Production of foam sheets> [Example 1] According to the formulation in Table 2, PET, PEI, talc MB and a crosslinking agent were mixed in a mixer to prepare a formulation. A circular die with a 93 mm diameter annular slit and a 0.6 mm slit width was set at the tip of a single-screw extruder (bore 65 mm, L / D=34), and a cylindrical cooling mandrel (diameter 206 mm, length 310 mm) was placed in front of the circular die in the extrusion direction. Cooling water was circulated inside the cooling mandrel. The extruder was set to a predetermined temperature, and the compound was kneaded in the extruder to obtain a molten mixture. A foaming agent (isobutane: normal butane = 35:65 (mass ratio)) was pressed into the middle of the extruder barrel and added to the molten resin, which was further kneaded to obtain a thermoplastic resin composition. The resin temperature during extrusion was set to 300°C, and the molten thermoplastic resin composition was extruded and foamed through the die slit of the circular die at a discharge rate of 30 kg / h to form a cylindrical foam. The cylindrical foam was expanded in diameter by a cooling mandrel and taken up by a take-up machine arranged further downstream of the cooling mandrel. The foam was cooled by placing the outer circumferential surface of the cooling mandrel along the inner circumferential surface of the foam, and the cylindrical foam was cut along the extrusion direction downstream of the cooling mandrel. The cylindrical foam was then cut into a flat strip and wound up into a roll by a take-up machine. The physical properties and evaluation of the obtained foam sheet are shown in Table 2.

[0148] [Examples 2 to 7, 9 to 18, Comparative Examples 1 to 4] Foamed sheets were produced in the same manner as in Example 1, except that the resin temperature during extrusion and the take-up speed of the take-up machine were adjusted according to the formulations in Tables 2 to 8. The physical properties and evaluations of the obtained foamed sheets are shown in Tables 2 to 8.

[0149] [Example 8] The foamed sheet obtained in Example 7 was pulverized to obtain flake-like resin, which was then remelted in a twin-screw extruder and extruded from a nozzle die in the form of strands. The strands were cooled and then pelletized to produce recovered pellets. A foamed sheet was produced in the same manner as in Example 1, except that the composition was as shown in Table 4. The properties and evaluation of the obtained foamed sheet are shown in Table 4.

[0150] <Production of fiber reinforced resin composite> Using the foamed sheet obtained in each example, a fiber-reinforced resin layer was laminated by the following method to prepare a fiber-reinforced resin composite.

[0151] A stainless steel plate was prepared as the mold 8 shown in FIG. 6, and a release agent (manufactured by Chemlease Japan, product name "Chemlease 2166") was applied to the upper surface of the stainless steel plate and left for one day, thereby performing a release treatment 81 on the upper surface of the stainless steel plate. As the fiber-reinforced resin layer, two sheets of the fiber-reinforced resin layer (A) or fiber-reinforced resin layer (B) shown in Tables 2 to 8 were prepared, and the two fiber-reinforced resin layers were stacked so that the fibers were oriented in the same direction, and placed on the release-treated surface of the stainless steel plate. Next, the foamed sheet obtained in each example was placed on the fiber-reinforced resin layer. Furthermore, two sheets of the fiber-reinforced resin layer (A) or fiber-reinforced resin layer (B) shown in Tables 2 to 8 were prepared, and the two fiber-reinforced resin layers were stacked so that the fibers were oriented in the same direction, and placed on the foamed sheet to produce a laminate.

[0152] Thereafter, a release film having through holes (manufactured by AIRTECH, product name "WL5200B-P") and a breather cloth (manufactured by AIRTECH, product name "AIRWEAVEN 4") were laminated in this order on the upper fiber reinforced resin layer of the laminate so as to cover the entire surface of the fiber reinforced resin layer. The breather cloth also covered both side surfaces (left and right side surfaces in FIG. 6) of the laminate. The release film was formed from a tetrafluoroethylene-ethylene copolymer film, and had many through holes that penetrated between both sides and allowed the thermosetting resin in the fiber reinforced resin layer to pass through. The breather cloth was formed from a nonwoven fabric composed of polyester-based resin fibers and was configured to be impregnated with a thermosetting resin. A bagging film (manufactured by AIRTECH, product name "WL7400") was placed on the laminate, and the outer edge of the bagging film was airtightly bonded to the stainless steel plate facing it using a sealant tape (manufactured by AIRTECH, product name "GS43MR") as a sealing material, sealing the laminate with the bagging film. The bagging film was made of nylon film. A back valve (manufactured by AIRTECH, product name "VACVALVE402A") was placed on a part of the bagging film to produce a laminate structure.

[0153] Next, the laminated structure was fed into an autoclave for heat curing tests (manufactured by Hanyuda Iron Works, product name "DL-2010"), the back valve of the laminated structure was connected to a vacuum line, and the space sealed with the bagging film was evacuated from the laminate in the direction of the breather cloth covering the side surface of the laminate to a vacuum degree of 0.10 MPa. Note that the decompression of the space was continued thereafter. Thereafter, the inside of the autoclave was pressurized to a gauge pressure of 0.1 MPa, the inside of the autoclave was heated to 90° C. at a temperature increase rate of 4° C. / min to heat the laminate, and the inside of the autoclave was heated at 90° C. for 20 minutes. This pressurization and heating softened the thermosetting resin in the fiber reinforced resin layer, deforming the fiber reinforced resin layer along the surface of the thermoplastic polyester-based resin foam layer, and also sucked and removed the air present in the fiber reinforced resin layer.

[0154] Next, the inside of the autoclave was pressurized to a gauge pressure of 0.3 MPa to apply a pressing force to the laminate, and the inside of the autoclave was heated to 130°C at a heating rate of 4°C / min to heat the laminate. The inside of the autoclave was heated at 130°C for 60 minutes to cure the thermosetting resin in the fiber reinforced resin layer, and the fiber reinforced resin layer was laminated and integrated on both sides of the foam sheet to obtain a fiber reinforced resin composite. Note that the excess thermosetting resin in the fiber reinforced resin layer was absorbed by the breather cloth through the through holes and the outside of the release film by pressurizing the laminate.

[0155] The autoclave was cooled to 60°C, and the pressure in the autoclave was released to return to atmospheric pressure, and the fiber-reinforced resin composite was taken out. The appearance of the fiber-reinforced resin composite was evaluated as described above, and the physical properties of the foamed sheet after compounding were also evaluated. The results are shown in Tables 2 to 8.

[0156] [Table 2]

[0157] [Table 3]

[0158] [Table 4]

[0159] [Table 5]

[0160] [Table 6]

[0161] [Table 7]

[0162] [Table 8]

[0163] As shown in Tables 2 to 8, Examples 1 to 18 in which the present invention was applied were given an overall evaluation of "good" to "good." On the other hand, the overall evaluation of Comparative Examples 1 and 2 in which the foamed sheet did not contain a polyimide resin and Comparative Examples 3 and 4 in which the glass transition temperature was not uniform was "x".

[0164] From the above results, it was confirmed that the application of the present invention can improve the heat resistance strength of a fiber-reinforced resin composite. [Explanation of symbols]

[0165] 2. Fiber-reinforced resin composite 5 Foam layer (foam sheet) 7 Fiber-reinforced resin layer

Claims

1. A sheet-like thermoplastic resin foam layer; A fiber reinforced resin layer located on one or both sides of the thermoplastic resin foam layer, the thermoplastic resin foam layer contains a polyester-based resin and a polyetherimide-based resin, The glass transition temperature Tg of the thermoplastic resin foam layer is single and is 80 to 130°C.

2. The thermoplastic resin foam layer has an absolute value of 3 to 35 J / g between the endothermic amount and the heat generation amount measured by heat flux differential scanning calorimetry at a heating rate of 10 ° C. / min. The fiber reinforced resin composite according to claim 1.

3. The slope of the exponential approximation equation of the storage modulus E' between the glass transition temperature Tg and the glass transition temperature Tg + 20 ° C. in solid viscoelasticity measurement at a heating rate of 5 ° C. / min and a frequency of 1 Hz is -0.18 to -0.

025. The fiber reinforced resin composite according to claim 1 or 2.

4. The fiber-reinforced resin composite according to any one of claims 1 to 3, wherein the polyester-based resin comprises a plant-derived polyester-based resin.

5. The content ratio of the polyester-based resin to the total mass of the thermoplastic resin contained in the thermoplastic resin foam layer is 40 to 95 mass%, The fiber reinforced resin composite according to any one of claims 1 to 4, wherein the content ratio of the polyetherimide resin to the total mass of the thermoplastic resin contained in the thermoplastic resin foam layer is 5 to 60 mass%.

6. The fiber reinforced resin composite according to any one of claims 1 to 5, wherein the thermoplastic resin foam layer contains recycled raw materials.

7. A fiber-reinforced resin composite having a sheet-like thermoplastic resin foam layer and a fiber-reinforced resin layer located on one or both sides of the thermoplastic resin foam layer. A thermoplastic resin foam sheet for a fiber-reinforced resin composite used to form the thermoplastic resin foam layer, the thermoplastic resin foam layer contains a polyester-based resin and a polyetherimide-based resin, The thermoplastic resin foam sheet for a fiber-reinforced resin composite, wherein the thermoplastic resin foam layer has a single glass transition temperature Tg of 80 to 130°C.

8. The thermoplastic resin foam sheet for fiber reinforced resin composites according to claim 7, wherein the absolute value of the difference between the endothermic amount and the heat generated by heat flux differential scanning calorimetry at a heating rate of 10 ° C. / min is 3 to 35 J / g.

9. The thermoplastic resin foam sheet for fiber reinforced resin composites according to claim 7 or 8, wherein the slope of the exponential approximation equation of the storage modulus E' between the glass transition temperature Tg and the glass transition temperature Tg + 20 ° C. in solid viscoelasticity measurement at a heating rate of 5 ° C. / min and a frequency of 1 Hz is -0.18 to -0.

025.

10. The thermoplastic resin foam sheet for fiber reinforced resin composites according to any one of claims 7 to 9, wherein the polyester-based resin comprises a plant-derived polyester-based resin.

11. The content ratio of the polyester-based resin to the total mass of the thermoplastic resin contained in the thermoplastic resin foam layer is 40 to 95 mass%, The content ratio of the polyetherimide resin to the total mass of the thermoplastic resin contained in the thermoplastic resin foam layer is 5 to 60 mass%. Thermoplastic resin foam sheet for fiber reinforced resin composites according to any one of claims 7 to 10.

12. The thermoplastic resin foam sheet for a fiber reinforced resin composite according to any one of claims 7 to 11, wherein the thermoplastic resin foam layer contains recycled raw materials.

Citation Information

Patent Citations

  • Molding of foamed polymethylene terephthalate sheet

    JP1991239527A

  • Foam and foam particle formed from polyester / polycarbonate resin composition

    JP2004182938A

  • Laminated polyester film

    JP2009056621A

  • Foamed and expandable high glass transition temperature polymers

    JP2009521548A

  • Thermoplastic polyester-based resin extruded foam sheet, molded artifact using the same, method for manufacturing a thermoplastic polyester-based resin extruded foam sheet, and fiber-reinforced composite

    JP2014028920A